The design of nine element quasi microstrip log periodic antenna - A. Rahim, Mohamad Kamal; Gardner, P. (IEEE, 2004)
This paper described the design, simulation and fabrication of the inset feed log periodic antenna with nine element. The antennas have been modeled using microstrip lines and S parameter data from individual single element. The data is extracted from the momentum simulation and combined with the microstrip transmission line. The properties of antennas such as bandwidth, gain, cross-polar isolation and half power beamwidth have been investigated and compared between simulation and measurements.A bandwidth up to 51% is achieved by using nine element arrays. The cross-polar isolation of the log periodic antenna is in the range of 10 to 30 dB. The typical half power beamwidth (HPBW) of the log periodic antenna is 40° for E plane and 60° for H plane. The gain of the antenna relative to the dipole antenna ranges from -3 dB to 5 dB © 2004 IEEE.